Screening for Dengue Virus Infection at GMMMC Hospital, Sukkur (Medical Forum Monthly, 2024)
Objective: Dengue is a severe arthropod borne viral disease characterized by fever, headache, retro – orbital pain, maculopapular rash, and thrombocytopenia. Disease is transmitted from one human to another by bite of infected Aedes aegypti mosquito. Disease now a days occurs in more than 100 countries worldwide. Study designed for screening suspected or probable cases to detect specific antibodies response in early stage of disease.Study Design: Cross sectional study. Place and Duration of Study: This study was conducted at Ghulam Muhammad Mahar Medical College Hospital, Sukkur from October, 2010 to October, 2012.Materials and Methods: Patients presenting with fever, bleeding tendencies, maculopapular rash or fever with thrombocytopenia were screened as per WHO criteria for suspected dengue infection. Blood was collected after 4 – 5 days of onset of illness. The serologic test was performed by using rapid immunochromatographic assay detection of anti dengue immunoglobulin M (IgM) antibodies.Results: 162 cases were screened for dengue infection. 16 (9.9 %) patients were positive with anti-dengue IgM. 12 patients were male and 04 were female. Platelets count was observed below 100 x 103 cmm3 in patients with dengue infection.Conclusion: Identification of dengue virus infection in early acute phase of disease is significant for morbidity and mortality screening of suspected cases and anti-mosquito eradication measures should be taken for breading sites of vector, mass education, and awareness programs may be initiated.